2014
DOI: 10.1111/jace.13271
|View full text |Cite
|
Sign up to set email alerts
|

The Sintering Trajectory and Electrical Properties of Niobium‐Doped Titania Sputtering Targets

Abstract: Nb-doped TiO 2 (TNO) films, which are highly conductive and transparent, can be used as transparent conductive oxide (TCO) films. A predominant manufacturing method for TCO film is magnetron sputtering, and the material of the sputtering target affects the performance of the film. The objective of this study was to investigate the sintering densification, microstructure, and electrical properties of TNO and TiO 2 sputtering targets. The results showed that the segregation of Nb at the grain boundary in TNO hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Given the importance of sputtering targets, the processes and properties of sputtering targets for TCO films have been extensively investigated, particularly those of AZO and gallium-doped zinc oxide (GZO) [20,21,[25][26][27][28][29][30][31][32][33][34][35][36][37]. Unfortunately, the process and characteristics of IGZO targets have been studied relatively little [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of sputtering targets, the processes and properties of sputtering targets for TCO films have been extensively investigated, particularly those of AZO and gallium-doped zinc oxide (GZO) [20,21,[25][26][27][28][29][30][31][32][33][34][35][36][37]. Unfortunately, the process and characteristics of IGZO targets have been studied relatively little [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…3. Moreover, in a previous study, energy dispersive X-ray analyses showed that the Nb contents inside the grain and at the grain boundary were 1.2 at% and 3.5 at%, respectively [15]. The segregation of Nb at the grain boundary can change the grain boundary energy, inhibit the grain growth, and facilitate the densification of TiO 2 ceramic [15].…”
Section: Resultsmentioning
confidence: 97%
“…The amounts of the dispersant and the binder were weighted according to the weight of the dry powder. The detailed procedures of slurry preparation were described in a previous study [15]. The as-prepared slurries were spray-dried with a spray dryer (L-8, Ohkawara Kakohki Co., Yokohama, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation